Before the baton musical direction and conducting in Stuart and Georgian Britain - Holman, Peter 1946- (Boydell & Brewer, 2020)
How was large-scale music directed or conducted in Britain before baton conducting took hold in the 1830s?
Title from publisher's bibliographic system (viewed on 21 Sep 2020)
Keywords: Geschichte 1603-1837; Conducting / Great Britain / History / 17th century; Conducting / Great Britain / History / 18th century; Music / Great Britain / 17th century / History and criticism; Music / Great Britain / 18th century / History and criticism; Dirigieren; Großbritannien